'You can't know, you're not 5': exploring children's views of what it is like to be in Primary 1 - Smith, Carol (The University of Edinburgh, 2023)
It is widely acknowledged that starting school is a significant time in most children’s lives, formatively impacting on cognitive, social, emotional, and physical development, health and wellbeing, and lifelong chances. The last three decades have witnessed a surge in national and international policy and research attention on early years educational provision and practice, where improving children’s experiences to ensure all children get the best start in life, has become a major focus. However, what this experience should involve in terms of effective practices, most especially in the earliest stages of beginning school, remains an area of debate. Little of this debate takes into consideration the perspectives of children themselves. By contrast, the study reported in this thesis set out to do exactly that. This study investigated the time when young children had begun compulsory education within a Scottish primary school context. Through the adoption of an ethnographic approach, it set out to gain an in-depth, contextually grounded, understanding of children’s every day, lived experiences of being in school based principally on how the children themselves talked about these experiences. The main participants in this study were 50 primary 1 children attending a single Scottish primary school. Over the course of a 10-month period, data for this study were primarily gathered through close observation, and the use of participatory activities, thus providing spaces for children to share their experiences, views, and perceptions of being in school. Building on processes of reflexive interpretive analysis, this thesis presents and discusses how the children talked of this time and explores what impacted on and shaped their experiences of being at school. The study found that the children’s day-to-day, lived experiences of school had had a profound impact upon their emergent conceptualisations of necessary ‘practices of being’ in school, which strongly linked to ‘practices of belonging’ and social positioning. From the wide array of findings, three principal themes are fore grounded for a closer discussion: children’s emergent sense of identity and belonging; bodily movements and choice; and opportunities for peer friendships. Most notably, it was found that the children commonly perceived of school as a place where you would be judged to be ‘right’ or ‘wrong’ in ways that became intrinsically linked to judgements on capabilities and belonging as a learner in school. A fragility in this sense of belonging emerged that impacted upon the children’s willingness to take risks in their learning, for fear of making mistakes or ‘getting it wrong’. On bodily movement and choice, the study highlights how the children experienced tensions between the systems and structures that regulated their bodily movements and their own preferences for freer movement in school spaces. On peer friendships, the thesis argues that the findings point up how a focus on socialisation within the school spaces needs to be widened out to provide opportunities for children to build, negotiate and maintain old and new peer friendships. Analysis of my observations and of children’s talk revealed how their reported experiences were imbricated in the school systems, structures, and design and use of spaces. Accordingly, the study necessarily involved a degree of examination of, and reflection on, current school systems. Drawing on the findings of this study, it is observed that one necessary element of a reconfiguration of early years education involves a refiguring of the architectural design and pedagogical use of school spaces that currently place an emphasis on order and control. It is observed that many school systems, structures and spatial organisational practices result in schools remaining firmly focused on notions of a ‘ready child’, where children believe their role is primarily to ‘fit in’. Following the lead of this thesis, seeking to foster children’s own voices and attend to their perspectives may act to undermine this conceptualisation of the ‘ready child’.
Keywords: school-based ethnography; primary 1; children’s experiences; practices of being; practices of belonging; social positioning; peer friendships